Online Lecture During Covid-19 Pandemic from College Students’ Perspective - Anita Indria; Hidayatul Dina; Meriyan Elza; Asmendri Asmendri; Milya Sari; Deni Asrida (AT-TA'LIM, 2021)
This research aims to analyze the obstacles of online learning during pandemic Covid-19. There have been pros and cons of online lecture during the pandemic due to lack of effectiveness of achieving education goals. However, education is expected to bring an improvement to students to be well-educated generation. To reach the goal, students must comprehend the materials given by lecturers. Yet, there are some problems that college students face during the process of online lecture. These problems became the background to conduct this research from which it can be a scientific work to give a contribution to analyze the problems specifically. This research was conducted by using qualitative method. The data were obtained by conducting interview which were analyzed and explained in the form of narration while maintaining the authenticity of the data. The result of this research revealed that limited internet access and lack of lecturers’ responsibilities became the obstacles for college students during online lecture. The students expected lecturers and campus staff to understand their situations. They hoped that the lecturers gave relevant deadline for submitting the assignments, focused on making the students understand the materials, and controlled/accompanied the flow of discussion